Dracaena draco L. fruit: phytochemical and antioxidant activity assessment - Silva, Branca M. (2016)
The present study reports for the first time the metabolite profile and antioxidant activity of aqueous extract obtained from Dracaena draco L. fruit. Volatiles profile was determined by HS-SPME/GC-IT-MS, with 9 compounds being identified, distributed by several distinct chemical classes: 1 alcohol, 3 aldehydes, 2 carotenoid derivatives, and 3 terpenic compounds. Aldehydes constituted the most abundant class in this exotic berry, representing 59% of total identified volatile compounds. Phenolics profile was determined by HPLC/DAD and 5 constituents were identified: 5-O-caffeoylquinic, 3,5-O-dicaffeoylquinic, ferulic and sinapic acids, and quercetin-3-O-rutinoside. The major phenolic compound is quercetin-3-O-rutinoside, comprising 42% of the total phenolic content. Organic acids composition was also characterized, by HPLC-UV, and oxalic, citric, L-ascorbic, malic, quinic and shikimic acids were determined. The most abundant is quinic acid, representing 39% of the total organic acid content. The antioxidant potential of this matrix was assessed by (i) reducing power of Fe3+/ferricyanide complex, (ii) scavenging effect on DPPH free radicals, and (iii) ability to inhibit the 2,2´-azobis(2-amidinopropane) dihydrochloride (AAPH)-induced oxidative hemolysis in human erythrocytes. Strawberry (Fragaria×ananassa Duch. cv. Camarosa) extract was used for comparison purposes. All assay models showed remarkable concentration dependent antioxidant activity, reducing power and radical scavenging efficiency for D. draco fruit, being invariably higher than that of strawberry extract. This is the first report showing that D. draco fruit is a promising new antioxidant agent.